Gestational Choriocarcinoma Presenting with Lacrimal Gland Metastasis: A First Reported Case - Naushad A. B. Ahamed; Khalid Sait; Nisreen Anfnan; Khader Farwan; S. H. M. Nizamuddin; Saleh S. Baeesa (Case Reports in Obstetrics and Gynecology)
Background. Gestational choriocarcinoma (GC) is a recognized clinicopathological subtype of gestational trophoblastic neoplasia that usually metastasizes hematogenously to highly vascular organs like the lung, liver, and brain. However, orbital metastasis to the choroid and lacrimal gland is a rare occurrence. Case Presentation. A 21-year-old female presented with headache and left orbital swelling one year after resection of a complete hydatidiform mole followed by adjuvant methotrexate chemotherapy. A metastatic imaging screening revealed multiple metastases in the lungs, brain, and adrenal gland, in addition to the choroid and lacrimal gland. Based on her modified WHO risk factors scoring she was started on chemotherapy and whole brain radiotherapy, which resulted in a complete response. At two-year follow-up, serum b-HCG level was with normal limits; imaging surveillance was uneventful. Conclusion. We present the first case of lacrimal gland metastasis in a young girl from GC relapse.